PERAN LEMBAGA DALAM PENGELOLAAN SAMPAH TERPADU DI KOTA PEKALONGAN - Iriani, Lia Yulia; Anggraini, Fitrijani; Prayudi, Tibin Ruby (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2015)
The solid waste is results from human activities or natural, if managed properly will be worth value, to add family income, otherwise if unmanaged will lead to problems as disease and environmental degradation. Current conditions environmental damage caused by solid waste in Pekalongan reached 39.9%. One the problems to need an integrated waste management is high rate of population increase 1.42% per year, the total population in 2012 amount 294,117 people.One the impact is waste generated by community and requires management. The waste reduction policy from source to the flagship program 3R (Reuse, Reduce, Recycling) and the objectives to achieve 20%, the previous study stated that the implementation of Indonesia’s waste can be reduced or used, less than 8%. Production of solid waste ± 768 m3/d and can be transported ± 614 m3/d, is still residual average daily ± 154 m3. The purpose of assessing the role of the institutional aspects of waste management, so that the economic value. The method used is an explanatory descriptive to test the influence between variables, the role of the principle and non-formal institutions, strategic indicators of waste management. The final conclusion illustrates that the role of non-formal institutions may help management of solid waste in Pekalongan approximately 79%, through recycling, so that solid waste into something useful and economically valuable. This requires a strategy and an active role of all parties such as governments as formal institutions, non-formal and public awareness in an effort to realize the waste becomes something useful.